The Internal Economic Developments and Its Impacts on Armenian Economy - Sargsyan, Karen («Ալվարդ Օհանջանյան Վառլենի»)
In the first quarter of 2025, the risks of economic growth slowdown and inflation acceleration in the global economy, as well as in Armenia’s main partner countries, have significantly increased due to the increase in prices of goods and services characterized by rigid prices in international commodity markets, the risks of possible disruption of supply value chains, as well as increasing tensions in international trade relations. Against the background of the above developments, it is expected that the central banks of leading countries will maintain relatively tight monetary conditions in the near future, in which case weak inflationary effects from the external sector may penetrate the RA economy. 2025 թ. առաջին եռամսյակում համաշխարհային տնտեսությունում, ինչպես նաև Հայաստանի հիմնական գործընկեր երկրներում տնտեսական աճի դանդաղման և գնաճի արագացման ռիսկերն էականորեն ավելացել են՝ կապված միջազգային ապրանքահումքային շուկաներում կոշտ գներով բնութագրվող ապրանքների և ծառայությունների գների աճով, առաջարկի արժեշղթաների հնարավոր խաթարման ռիսկերով, ինչպես նաև միջազգային առևտրային հարաբերություններում աճող լարվածությամբ: Նշված զարգացումների ֆոնին ակնկալվում է, որ առաջատար երկրների կենտրոնական բանկերն առաջիկայում կպահպանեն դրամավարկային համեմատաբար խիստ պայմանները, ինչի պարագայում՝ արտաքին հատվածից ՀՀ տնտեսության վրա հնարավոր են թույլ գնաճային ազդեցությունների ներթափանցում: В первом квартале 2025 года риски замедления экономического роста и ускорения инфляции в мировой экономике, а также в основных странах- партнерах Армении существенно возросли из-за роста цен на товары и услуги, характеризующиеся жесткими ценами на международных товарных рынках, рисков возможного нарушения цепочек создания стоимости поставок, а также из-за усиления напряженности в международных торговых отношениях. На фоне вышеизложенных событий ожидается, что центральные банки ведущих стран в ближайшем будущем сохранят относительно жесткие денежно- кредитные условия, в результате чего слабые инфляционные влияния из внешнего сектора могут проникнуть в экономику РА.
Keywords: Economics